Observational Cohort Study of Oral Mycobiome and Interkingdom Interactions over the Course of Induction Therapy for Leukemia - Sarah Robinson (American Society for Microbiology, 2020)
ABSTRACT Although the term “microbiome” refers to all microorganisms, the majority of microbiome studies focus on the bacteriome. Here, we characterize the oral mycobiome, including mycobiome-bacteriome interactions, in the setting of remission-induction chemotherapy (RIC) for acute myeloid leukemia (AML). Oral samples (n = 299) were prospectively collected twice weekly from 39 AML patients during RIC until neutrophil recovery. Illumina MiSeq 16S rRNA gene (V4) and internal transcribed spacer 2 (ITS2) sequencing were used to determine bacterial and fungal diversity and community composition. Intrakingdom and interkingdom network connectivity at baseline (T1) and at midpoint (T3) and a later time point (T6) were assessed via SPIEC-EASI (sparse inverse covariance estimation for ecological association inference). In this exploratory study, mycobiome α-diversity was not significantly associated with antibiotic or antifungal receipt. However, postchemotherapy mycobiome α-diversity was lower in subjects receiving high-intensity chemotherapy. Additionally, greater decreases in Malassezia levels were seen over time among patients on high-intensity RIC compared to low-intensity RIC (P = 0.003). A significantly higher relative abundance of Candida was found among patients who had infection (P = 0.008), while a significantly higher relative abundance of Fusarium was found among patients who did not get an infection (P = 0.03). Analyses of intrakingdom and interkingdom relationships at T1, T3, and T6 indicated that interkingdom connectivity increased over the course of IC as bacterial α-diversity diminished. In (to our knowledge) the first longitudinal mycobiome study performed during AML RIC, we found that mycobiome-bacteriome interactions are highly dynamic. Our study data suggest that inclusion of mycobiome analysis in the design of microbiome studies may be necessary to optimally understand the ecological and functional role of microbial communities in clinical outcomes. IMPORTANCE This report highlights the importance of longitudinal, parallel characterization of oral fungi and bacteria in order to better elucidate the dynamic changes in microbial community structure and interkingdom functional interactions during the injury of chemotherapy and antibiotic exposure as well as the clinical consequences of these interrelated alterations.